Meteorological conditions and avalanche danger of winters in the Caucasus at the end of the 21st century based on the results of CMIP6 models - I. A. Korneva; A. D. Oleynikov; P. A. Toropov; N. E. Varentsova; N. V. Kovalenko (Лëд и снег)
The paper considers a forecast of avalanche danger in the Caucasus at the end of the 21st century based on the climatic avalanche indicator criterion developed at Moscow State University, using the results of the CMIP6 Earth System Models (ESM). The quality of models’ estimates of modern winter climate in the Caucasus has been evaluated. The best models were selected, for which the average temperature error is –0.6 °C, precipitation error is 10 %. According to these models’ data, by the end of the XXI century the average winter air temperature in the Caucasus will be 4–6 °C higher than the present one, and the precipitation sum will exceed the modern value by 25 %. The frequency of seasons with extreme moisture will increase 2–3 times (monthly precipitation more than 100 mm). The seasonal maximum precipitation at the end of the 21st century will shift to March, while extremely dangerous avalanche winters are usually accompanied by a January maximum precipitation with a significant negative temperature anomaly. Experiments were also conducted with the numerical model SNOWPACK, which showed that despite the positive precipitation anomaly and the possible occurrence of cold winters, the most typical situation by the end of the 21st century will be the formation of a homogeneous snow column with low density, or heavily watered snow cover. Both situations are not avalanche-prone. Therefore, the background forecast of avalanche danger for the years 2071–2100 can be formulated as follows: a significant decrease in the frequency of the most destructive large avalanches from dry snow in high-mountain areas and their disappearance in mid-mountain areas, and a tendency to an increase in the number of less dangerous avalanches from loose and wet snow.